Problems preventing air companies from efficient investment activities - Arljukova, Irina (Technological and Economic Development of Economy, 2008)
The article deals with the problems of investment development of air companies. The author examines the aspects of modelling of investment solutions under conditions of developing aviation business, giving methods of modelling of demand, including those based on dynamics of macroeconomic indicators. The article contains the problems relating to assessment of macroeconomic risks, using models of assessment of discount rates. Variants of assessment of currency risks in the process of evaluation of efficiency of international investment solutions are analyzed as well. This article also deals with some problems relating to project financing. The aspect on necessity to take into account correlation between man’s potentiality and equipment capacity in the process of development of investment activities of air companies is discussed as well. Aviakompanijų investicinės veiklos efektyvumo problemų prevencija Santrauka. Straipsnyje nagrinėjamos aviakompanijų investicijų plėtros problemos. Autorė tyrinėja investicinių sprendimų modeliavimo aspektus aviacijos verslo plėtros sąlygomis. Pateikiami paklausos modeliavimo metodai, tarp kurių yra nagrinėjančių makroekonomikos rodiklių dinamiką. Straipsnyje aptariamos makroekonominės rizikos įvertinimo problemos taikant modelius, įvertinančius diskonto normą. Taip pat nagrinėjami valiutos rizikos variantai tarptautinių investicinių sprendimų efektyvumo įvertinimo proceso kontekste. Šiame straipsnyje taip pat gvildenamos kai kurios projekto finansavimo problemos. Diskutuojama, ar aviakompanijų investicijų plėtros procese būtina įvertinti tarpusavio ryšį tarp apsirūpinimo žmogiškaisiais ištekliais ir įranginiais. Reikšminiai žodžiai: investavimas, rizika, modeliavimas, diskontavimas, konversija, finansavimas, galimybės, efektyvumas. First published online: 21 Oct 2010